Treatment of RET-positive advanced medullary thyroid cancer with multi-tyrosine kinase inhibitors: a retrospective multi-center registry analysis - Köhler, Viktoria Florentine; Adam, Pia; Fuß, Carmina Teresa; Jiang, Linmiao; Berg, Elke; Frank-Raue, Karin; Raue, Friedhelm; Hoster, Eva; Knösel, Thomas; Schildhaus, Hans-Ulrich; Negele, Thomas; Siebolts, Udo; et al. (Cancers, 2022)
Background: RET (rearranged during transfection) variants are the most prevalent oncogenic events in medullary thyroid cancer (MTC). In advanced disease, multi-tyrosine kinase inhibitors (MKIs) cabozantinib and vandetanib are the approved standard treatment irrespective of RET status. The actual outcome of patients with RET-positive MTC treated with MKIs is ill described. Methods: We here retrospectively determined the RET oncogene variant status with a targeted DNA Custom Panel in a prospectively collected cohort of 48 patients with advanced MTC treated with vandetanib and/or cabozantinib at four German referral centers. Progression-free survival (PFS) and overall survival (OS) probabilities were estimated using the Kaplan-Meier method. Results: In total, 44/48 (92%) patients had germline or somatic RET variants. The M918T variant was found in 29/44 (66%) cases. In total, 2/32 (6%) patients with a somatic RET variant had further somatic variants, while in 1/32 (3%) patient with a germline RET variant, additional variants were found. Only 1/48 (2%) patient had a pathogenic HRAS variant, and no variants were found in 3 cases. In first-line treatment, the median OS was 53 (95% CI (95% confidence interval), 32-NR (not reached); n = 36), and the median PFS was 21 months (12-39; n = 33) in RET-positive MTC patients. In second-line treatment, the median OS was 18 (13-79; n = 22), and the median PFS was 3.5 months (2-14; n = 22) in RET-positive cases. Conclusions: RET variants were highly prevalent in patients with advanced MTC. The treatment results in RET-positive cases were similar to those reported in unselected cohorts.
medullary thyroid cancer; rearranged during transfection; variant; multi-tyrosine kinase inhibitor; survival; treatment outcome